Memorandum of Understanding between NHSBT, UK and Multi Organ Harvesting Aid Network Foundation, Chennai, India. (July 2018) - Krishnan, Nithya Santhana; Sharif, Adnan; Ploeg, Rutger; Nagiyan, Sridhar; Shroff, Sunil
Abstract : N/A: Multi-Organ Harvesting Aid Network (MOHAN) Foundation (MF) entered into a landmark Memorandum of Understanding (MoU) with NHS Blood and Transplant (NHSBT), UK in January 2015 and was reaffirmed at the House of Lords in February 2016. The objective of the MoU was to promote collaboration and knowledge sharing between the two organizations with the aim of increasing organ donation rates in India and in the UK. Many successful joint ventures have materialized since the MoU was signed. Collaborative working and sharing of good practices have had a positive impact in improving donation rates in both countries. Members of each organization meet annually to discuss, share and implement ideas to help improve organ donation rates. MF assists NHSBT in improving organ donation rates among Black, Asian and Minority Ethnic (BAME) communities in the UK and NHSBT helps MF in increasing deceased donation rates in India. Deceased donor transplantation is in its' infancy in India. There is no structured training for organ retrieval in India. Hence following the MoU, National Organ Retrieval Course was started in India with the help of surgeons from Oxford and Birmingham to help increase deceased donation rates in India. Effective maintenance and optimization of a potential organ donor remains a universal challenge. Donor Optimisation App is an offshoot of the collaboration. This app (Photographs 1 & 2) was developed, in India in partnership with MOHAN Foundation, to enable medical and paramedical personnel to have instant access to the latest evidence-based guidelines for the management of potential organ donors. The app is being used by the healthcare professionals in both countries. The app is available for Android and iPhones and can be downloaded from the MOHAN Foundation website –www.mohanfoundation.org . Figure. No caption available.